Quantitative assessment of angiogenesis and pericyte coverage in human cell-derived vascular sprouts. Issue 1 (December 2017) - Eglinger, Jan; Karsjens, Haiko; Lammert, Eckhard
Abstract Background Pericytes, surrounding the endothelium, fulfill diverse functions that are crucial for vascular homeostasis. The loss of pericytes is associated with pathologies, such as diabetic retinopathy and Alzheimer's disease. Thus, there exists a need for an experimental system that combines pharmacologic manipulation and quantification of pericyte coverage during sprouting angiogenesis. Here, we describe an in vitro angiogenesis assay that develops lumenized vascular sprouts composed of endothelial cells enveloped by pericytes, with the additional ability to comparatively screen the effect of multiple small molecules simultaneously. For automated analysis, we also present an ImageJ plugin tool we developed to quantify sprout morphology and pericyte coverage. Methods Human umbilical vein endothelial cells and human brain vascular pericytes were coated on microcarrier beads and embedded in fibrin gels in a 96-well plate to form lumenized vascular sprouts. After treatment with pharmacologic compounds, sprouts were fixed, stained, and imaged via optical z-sections over the area of each well. The maximum intensity projections of these images were stitched together to form montages of the wells, and those montages were processed and analyzed. Results Vascular sprouts formed within 4–12 days and contained a patent lumen surrounded by a layer of human endothelial cells and pericytes. Using our workflow and image analysis, pericyte coverage after treatment with various compounds was successfully quantified. Conclusions Here we present a robust in vitro assay using primary human vascular cells that allows researchers to analyze the effects of multiple compounds on sprouting angiogenesis and pericyte coverage. Our ImageJ plugin offers automated evaluation across multiple different vascular parameters, such as sprout length, cell density, branch points, and pericyte coverage.